A Comprehensive Review of Sociolinguistics and Psycholinguistics: Exploring Language, Society, and the Mind - Mishra, Meghana (Journal of Advanced Research in English & Education, 2024)
Sociolinguistics and psycholinguistics are two pivotal disciplines in the study of language, addressing the intricate interplay between language, society, and the human mind. While sociolinguistics focuses on the social aspects of language use, psycholinguistics examines the cognitive and psychological processes involved in language acquisition and processing. These disciplines provide essential insights into how linguistic patterns are influenced by cultural norms, power dynamics, and cognitive mechanisms. This review article explores the foundational theories, contemporary research trends, and future directions in these fields. It highlights the role of sociolinguistics in understanding language variation, identity formation, and social interactions, as well as the contribution of psycholinguistics in decoding the neurological and psychological underpinnings of language processing and multilingualism. By examining their interconnections and distinct contributions, the article underscores their significance in advancing our understanding of language as a multifaceted phenomenon and its implications for societal and cognitive development.